2015
DOI: 10.3892/ol.2015.4059
|View full text |Cite
|
Sign up to set email alerts
|

Reversible posterior leukoencephalopathy syndrome following combinatorial cisplatin and pemetrexed therapy for lung cancer in a normotensive patient: A case report and literature review

Abstract: Abstract. Reversible posterior leukoencephalopathy syndrome (RPLS) is a rare neurological syndrome of the brain, causing symptoms such as headaches, seizures, altered mental status and visual disturbances. The condition is predominantly associated with hypertension, eclampsia, renal impairment, cytotoxic drugs, immunosuppressive agents and molecular targeted agents, but the precise underlying mechanism of RPLS is not fully understood. The present study describes the case of a 65-year-old female patient with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Acute Marchiafava-Bignami disease (Wenz et al, 2014) in alcoholic patients, the early stages of 5-fluorouracil-induced leukoencephalopathy (Bang et al, 2012) in cancer patients, hypoglycemic encephalopathy (Ma et al, 2009), and reversible posterior leukoencephalopathy syndrome (Xie and Jones, 2016) may have similar patterns of lesions in the corpus callosum and white matter on MRI. However, occupational history and clinical characteristics can differentiate these conditions from leukoencephalopathy due to organotin intoxication.…”
Section: Discussionmentioning
confidence: 97%
“…Acute Marchiafava-Bignami disease (Wenz et al, 2014) in alcoholic patients, the early stages of 5-fluorouracil-induced leukoencephalopathy (Bang et al, 2012) in cancer patients, hypoglycemic encephalopathy (Ma et al, 2009), and reversible posterior leukoencephalopathy syndrome (Xie and Jones, 2016) may have similar patterns of lesions in the corpus callosum and white matter on MRI. However, occupational history and clinical characteristics can differentiate these conditions from leukoencephalopathy due to organotin intoxication.…”
Section: Discussionmentioning
confidence: 97%
“…In the present case, a 7-day interruption in therapy allowed for the resolution of PRES symptoms and MRI findings, suggesting that lenvatinib treatment was the cause of PRES. One study suggested that severe hypertension causing vasogenic edema can also precipitate PRES ( 20 ). It is unlikely that PRES was directly caused by severe hypertension - independent of lenvatinib use - in the present case, as the PRES symptoms disappeared during the suspension of lenvatinib treatment and reappeared after its re-initiation, despite the patient's recurrent severe hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Since the present case of PRES was a patient treated with CDDP/Pem, it is difficult to determine which anticancer drug was responsible. In 2016, Xie and Jones [ 9 ] reported a case of PRES associated with CDDP/Pem, which was concluded to be caused by CDDP based on the absence of previous reports of PRES related to Pem alone. In 2009, Nguyen et al [ 10 ] also reported a case of PRES associated with CDDP/Pem, which was attributed to neurotoxicity of CDDP enhanced by dexamethasone for treating nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%